Looking forwards and backwards: The real-time processing of Strong and Weak Crossover. Issue 1 (31st July 2017) - Kush, Dave; Lidz, Jeffrey; Phillips, Colin
Abstract : We investigated the processing of pronouns in Strong and Weak Crossover constructions as a means of probing the extent to which the incremental parser can use syntactic information to guide antecedent retrieval. In Experiment 1 we show that the parser accesses a displaced wh-phrase as an antecedent for a pronoun when no grammatical constraints prohibit binding, but the parser ignores the same wh-phrase when it stands in a Strong Crossover relation to the pronoun. These results are consistent with two possibilities. First, the parser could apply Principle C at antecedent retrieval to exclude the wh-phrase on the basis of the c-command relation between its gap and the pronoun. Alternatively, retrieval might ignore any phrases that do not occupy an Argument position. Experiment 2 distinguished between these two possibilities by testing antecedent retrieval under Weak Crossover. In Weak Crossover binding of the pronoun is ruled out by the argument condition, but not Principle C. The results of Experiment 2 indicate that antecedent retrieval accesses matching wh-phrases in Weak Crossover configurations. On the basis of these findings we conclude that the parser can make rapid use of Principle C and c-command information to constrain retrieval. We discuss how our results support a view of antecedent retrieval that integrates inferences made over unseen syntactic structure into constraints on backward-looking processes like memory retrieval.